1997
DOI: 10.1111/j.1532-5415.1997.tb02930.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental Status, Quality of Life, and Mortality in an Older Community Population: A Multivariate Approach

Abstract: Within this cohort of 70 to 75-year-old urban residents, FDS is associated with several QOL domains and with long-term survival. A hierarchy of reciprocal relationships exists among these parameters. The present study provides a basis for encouraging more extensive use of dentures. Longitudinal studies using oral health outcomes are warranted before clinical recommendations can be made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
83
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 45 publications
6
83
0
5
Order By: Relevance
“…Therefore, denture use was taken as proxy. As to the eligibility of denture-related studies, one investigation [59] was excluded, being based on data also used in another publication [37]. Two studies reported no quantitative data and were, therefore, not included [57,60].…”
Section: General Description Of Selected Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, denture use was taken as proxy. As to the eligibility of denture-related studies, one investigation [59] was excluded, being based on data also used in another publication [37]. Two studies reported no quantitative data and were, therefore, not included [57,60].…”
Section: General Description Of Selected Studiesmentioning
confidence: 99%
“…Similarly, the follow-up times differed and were at minimum 5 [43] or 6 years [47] and at maximum 57 years [56] in studies on all-cause or circulatory mortality (Table 1). In studies exploring the putative relation between denture use and mortality (Table 2), there were shorter observation periods of 4 [38] to 15 years [37].…”
Section: General Description Of Selected Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Prosthodont Res Pract 5 : [2][3][4][5][6][7][8][9]2006 To achieve greater recognition for prosthodontics in academia and among the general public as a vital health science specialty for the 21st century, and to advance this specialty's contributions to society, the Japan Prosthodontic Society has become a corporate juridical person. Today, our organization stands ready to accept the responsibility for leadership in developing initiatives to improve prosthodontic education, research, and treatment.…”
Section: Yasumasa Akagawa President Of Japan Prosthodontic Societymentioning
confidence: 99%
“…For example, research has shown that independent elderly with more than 16/20 teeth live significantly longer. 9,10 Those elderly whose lost teeth and impaired occlusion have not been restored with dentures have a significantly lower rate of survival than those whose lost teeth and occlusion have been restored 11 (Fig. 4).…”
Section: Evidence Of the Value Of Prosthodonticsmentioning
confidence: 99%